(untitled) (International Educators Conference, 2025)
This article explores the psychological aspects of developing adolescents’ reflective skills, emphasizing the importance of self-awareness and critical thinking in the learning process. It discusses how these skills contribute to personal growth and decision-making, focusing on the psychological mechanisms involved in reflective practice. The study highlights various psychological approaches and methods to enhance these skills, aiming to improve adolescents’ ability to analyze and evaluate their experiences effectively. The article provides insights into the role of educators and psychological support in fostering a reflective mindset among young learners.